Managing human resources in Sarawak: The organizational support perspectives - Lew, Tek (Curtin University Sarawak Campus, 2010)
Managing human resources (HR) in Sarawak is challenging due to the dynamic mix of human resources (HR) in organizations and there is a lack of studies on how to effectively manage HR in contemporary Sarawak. Hence, the main objective of this conceptual paper is to discuss the influence of selected human resource management (HRM) practices, namely pay satisfaction, career development opportunities and work/family support on the affective organizational commitment and turnover intention of employees which may guide studies in the HRM discipline in Sarawak in the future. This paper is driven theoretically by the social exchange theory, the concept of perceived organizational support (POS) which is the commitment of the organization to the employee, the norm of reciprocity, the organizational support theory as well as the other relevant literature in the human resource management and organizational behaviour research. This paper has the potential to contribute to the limited body of knowledge about the psychological processes underlying the formation of organizational commitment through the perspectives of the social exchange theory and the organizational support theory especially in the context of managing HR for professionals in Sarawak.